2020
DOI: 10.1093/ijnp/pyaa005
|View full text |Cite
|
Sign up to set email alerts
|

Prescribing Patterns of Psychotropic Drugs and Risk of Violent Behavior: A Prospective, Multicenter Study in Italy

Abstract: Background This prospective cohort study aimed at evaluating patterns of polypharmacy and aggressive and violent behavior during a 1-year follow-up in patients with severe mental disorders. Methods A total of 340 patients (125 inpatients from residential facilities and 215 outpatients) were evaluated at baseline with the Structured Clinical Interview for DSM-IV Axis I and II, Brief Psychiatric Rating Scale, Specific Levels of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 59 publications
1
6
1
Order By: Relevance
“… 36 Using a specific analytical methodology which made it possible to control the large number of MOAS ratings equal to 0, a linear increase in MOAS ratings was observed, especially in participants with a history of violence, who exhibited more aggressive and violent behaviour than those with no history of violence. 52 …”
Section: Discussionmentioning
confidence: 99%
“… 36 Using a specific analytical methodology which made it possible to control the large number of MOAS ratings equal to 0, a linear increase in MOAS ratings was observed, especially in participants with a history of violence, who exhibited more aggressive and violent behaviour than those with no history of violence. 52 …”
Section: Discussionmentioning
confidence: 99%
“…Being in a forensic facility implies that patients had guaranteed pharmacological treatment, which promotes clinical stabilization, symptoms reduction, and a better course of the disorder. Moreover, some studies have shown that ensuring treatment compliance decreases the risk of violence [ 66 68 ].…”
Section: Discussionmentioning
confidence: 99%
“…Being in a forensic facility implies that patients had guaranteed pharmacological treatment, which promotes clinical stabilization, symptoms reduction, and a better course of the disorder. Moreover, some studies have shown that ensuring treatment compliance decreases the risk of violence [66][67][68]. Nevertheless, many clinical characteristics of patients included in our meta-analysis were unspecified, and this makes it difficult to draw precise conclusions.…”
Section: Clinical Characteristics Of Patients Studied In Forensic Set...mentioning
confidence: 98%
“…Nevertheless, this finding is in agreement with studies among non-forensic psychiatric inpatients reporting a reduction of aggressive behavior among patients treated with clozapine. 14,[29][30][31][32] The effects of risperidone were studied in two studies. Gibbon et al 21 retrospectively investigating the clinical charts of 118 patients for the effects of RLAI and found that 25% experienced a reduction in violent incidents, but this study did not use a control group.…”
Section: Type Of Antipsychoticsmentioning
confidence: 99%